Moral Education and Physical Education: A Systematic Literature Review (JURNAL PENDIDIKAN JASMANI DAN OLAHRAGA, 2024)
Currently, a lot of anti-moral behaviors occur among students at school. The aim of this article was to provide a better understanding of how physical education can be used as a mean to develop moral values in individuals. Research trends and future research directions are also discussed further in this research. A systematic literature review method was used by applying inclusion and exclusion criteria. There were various criteria set in this research. Of the 37 articles found, only 9 articles met the criteria to be included in further analysis. The results of this research explored three components, namely research trends in the field of physical education and moral education, the relationship between physical education and moral education, and future research directions related to physical education and moral education. The relationship between physical education and moral education still has pros and contras due to the research result variations. Further studies are needed to confirm the theory related to this study. Research involving diverse sample backgrounds is highly recommended for future research.